A Divergent Strain of Culex pipiens-Associated Tunisia Virus in the Malaria Vector Anopheles epiroticus - Debat, Humberto Julio (2018)
Here, we report the draft genome sequence of a divergent strain ofCulex pipiens-associated Tunisia virus (CpATV) identified in the malaria vectorAnoph-eles epiroticus(CpATV-AnE). CpATV-AnE expands the reference virus sequence, intro-ducing an extended replicase with novel virga-like domains. Our results suggest thatthe host range of CpATV includesAnophelessp. mosquitoes.